Pengaruh Degree of Financial Leverage dan Degree of Operating Leverage Terhadap Profitabilitas - Ni Made Dwi Puspitasari; G. Oka Warmana; Ni Putu Yeni Astiti (UNHI Press, 2020)
Leverage is the use of assets and sources of funds that incur fixed costs, which aim to increase the potential returns of shareholders. This study aims to determine the effect of degree of financial leverage and degree of operating leverage on profitability. The sample of this study was 19 transportation companies listed on the Indonesia Stock Exchange in 2015-2017. The data is analyzed by multiple linear regression. The test results show that: 1) Financial Leverage has a negative and significant effect on profitability; 2) Operating Leverage has a positive and significant effect on profitability. Based on these findings, it is suggested that the company can use the operating leverage to improve profitability, but to be careful in the use of financial leverage because it can reduce profitability.